A human development index by income groups - Michael Grimm; Kenneth Harttgen; Stephan Klasen; Mark Misselhorn (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
One of the most frequent critiques of the HDI is that is does not take into account inequality within countries in its three dimensions. We suggest a relatively easy and intuitive approach which allows to compute the three components and the overall HDI for quintiles of the income distribution. This allows to compare the level in human development of the poor with the level of the non-poor within countries, but also across countries. An empirical illustration for a sample of 13 low and middle income countries and 2 industrialized countries shows that inequality in human development within countries is indeed high. The results also show that the level of inequality is only weakly correlated with the level of human development itself.
Keywords: 330; Entwicklungsindikator; Disparitätsmaß; Einkommensverteilung; Bildungschancen; Sterblichkeit; Entwicklungsländer; Afrika